Evaluation of the Effects of Installation Faults in the Outdoor Unit of Air Conditioners Using Exergy Analysis - Ergen, Ruveyda; Gürtürk, Mert (My University, 2025)
The increasing prevalence of global warming has led to a significant rise in the use of air conditioning systems, a trend widely acknowledged by numerous key institutions. However, this widespread adoption has brought about several challenges, particularly those stemming from improper installation practices. This study specifically examines the impact of installation faults in the condenser units of air conditioners on exergy destruction. One of the most critical issues identified is the blockage of the air inlet in the condenser unit, which often occurs due to installation errors. This study investigates the effects of such blockages on exergy destruction within the system. The findings indicate that installation faults in the condenser unit can substantially reduce the exergy efficiency of air conditioning systems, with efficiency values ranging from 38% to as low as 19%. Moreover, the exergy analysis of the condenser unit reveals that under inefficient operating conditions, exergy destruction increases by 114%. For example, when the air inlet of the condenser is obstructed, the exergy destruction in this section escalates from 0.35 kW to 0.75 kW, underscoring the critical impact of improper installation on system performance.
Keywords: Exergy; Air conditioning; Installation Fault